Effects of mistletoe (Phoradendron villosum) on California oaks. (20th June 2018) - Koenig, Walter D.; Knops, Johannes M. H.; Carmen, William J.; Pesendorfer, Mario B.; Dickinson, Janis L.
Abstract : Mistletoes are a widespread group of plants often considered to be hemiparasitic, having detrimental effects on growth and survival of their hosts. We studied the effects of the Pacific mistletoe, Phoradendron villosum, a member of a largely autotrophic genus, on three species of deciduous California oaks. We found no effects of mistletoe presence on radial growth or survivorship and detected a significant positive relationship between mistletoe and acorn production. This latter result is potentially explained by the tendency of P. villosum to be present on larger trees growing in nitrogen-rich soils or, alternatively, by a preference for healthy, acorn-producing trees by birds that potentially disperse mistletoe. Our results indicate that the negative consequences of Phoradendron presence on their hosts are negligible—this species resembles an epiphyte more than a parasite—and outweighed by the important ecosystem services mistletoe provides.